Investigation of the mechanical and hydrodynamic behavior of lock gates under high head conditions - Liu, Yongsheng; Wang, Neng; Kuang, Tao; Ye, Yasi; Niu, Jiye; Cai, Jianguo (Frontiers in Built Environment, 2025)
As a core component of the lock filling and emptying system, the operational performance of the valve significantly influences the efficiency and safety of navigation locks. To elucidate the mechanical mechanisms during valve operation, this study investigates the valve structure of the Hongjiang hub under high head conditions. A combined approach of numerical simulation and scale experiment was employed to examine both the mechanical response and hydrodynamic behaviors of the valve. (1) Numerical results indicate the stress concentration is easy to occur in the center of the bottom panel of the valve, which causes the structural displacement. Structural checks confirm that both stress and displacement remain within the allowable design limits, demonstrating the structural adequacy of the valve. The valve’s natural frequency is substantially higher than the dominant energy range of flow-induced excitations, suggesting a low likelihood of severe vibration. (2) Experimental investigations were conducted to evaluate the valve’s hydrodynamic characteristics. Pressure fluctuations on the valve surface were found to be strongly correlated with the valve opening. At small openings, the valve body lies within a high-velocity jet zone formed by the gap between the valve and the sill, resulting in pronounced pressure fluctuations. As the opening increases, the valve body shifts into the valve chamber, and measured pressures become more stable, with reduced fluctuation amplitudes. (3) During the opening process, the opening force initially increases and then decreases, with a peak value of approximately 200 kN. In contrast, the closing force during valve closure follows a “decrease–increase–decrease” trend, reaching a minimum of around −150 kN. (4) Un-der emergency closure conditions at an opening ratio of n = 0.3, the hydrodynamic load coefficient peaks at approximately 1.22. The effect of the valve opening speed on the dynamic load is found to be negligible. The findings provide theoretical insights and practical guidance for the design and manufacture of lock valves operating under high head conditions.